The Galileo Project put to the test of European competition and public procurement law - Markus C. Kerber (Intereconomics, 2010)
The following article throws some light on the (fragile) legal foundations of the Galileo Project, the European Satellite Navigation System, and gives an interpretation of the normative procurement rules of the EU. Additionally it tries to reveal the practical problems of upholding the principle of free competition and an open market in as much as the procurement of high technology concerns a highly olipolistic market.
Keywords: 330